Answer:
1) The equation of the line in slope-intercept form is
. The equation of the line in standard form is
.
2) The equation of the line in slope-intercept form is
. The equation of the line in standard form is
.
3) The equation of the line in slope-intercept form is
. The equation of the line in standard form is
.
4) The equation of the line in slope-intercept form is
. The equation of the line in standard form is
.
5) The equation of the line in slope-intercept form is
. The equation of the line in standard from is
.
Step-by-step explanation:
1) We begin with the slope-intercept form and substitute all known values and calculate the y-intercept: (
,
,
)
![4 = (5)\cdot (-1)+b](https://tex.z-dn.net/?f=4%20%3D%20%285%29%5Ccdot%20%28-1%29%2Bb)
![4 = -5 +b](https://tex.z-dn.net/?f=4%20%3D%20-5%20%2Bb)
![b = 9](https://tex.z-dn.net/?f=b%20%3D%209)
The equation of the line in slope-intercept form is
.
Then, we obtain the standard form by algebraic handling:
![-5\cdot x + y = 9](https://tex.z-dn.net/?f=-5%5Ccdot%20x%20%2B%20y%20%3D%209)
The equation of the line in standard form is
.
2) We begin with a system of linear equations based on the slope-intercept form: (
,
,
,
)
(Eq. 1)
(Eq. 2)
From (Eq. 1), we find that:
![b = 4-3\cdot m](https://tex.z-dn.net/?f=b%20%3D%204-3%5Ccdot%20m)
And by substituting on (Eq. 2), we conclude that slope of the equation of the line is:
![-2\cdot m +4-3\cdot m = 2](https://tex.z-dn.net/?f=-2%5Ccdot%20m%20%2B4-3%5Ccdot%20m%20%3D%202)
![-5\cdot m = -2](https://tex.z-dn.net/?f=-5%5Ccdot%20m%20%3D%20-2)
![m = \frac{2}{5}](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7B2%7D%7B5%7D)
And from (Eq. 1) we find that the y-Intercept is:
![b=4-3\cdot \left(\frac{2}{5} \right)](https://tex.z-dn.net/?f=b%3D4-3%5Ccdot%20%5Cleft%28%5Cfrac%7B2%7D%7B5%7D%20%5Cright%29)
![b = 4-\frac{6}{5}](https://tex.z-dn.net/?f=b%20%3D%204-%5Cfrac%7B6%7D%7B5%7D)
![b = \frac{14}{5}](https://tex.z-dn.net/?f=b%20%3D%20%5Cfrac%7B14%7D%7B5%7D)
The equation of the line in slope-intercept form is
.
Then, we obtain the standard form by algebraic handling:
![-\frac{2}{5}\cdot x +y = \frac{14}{5}](https://tex.z-dn.net/?f=-%5Cfrac%7B2%7D%7B5%7D%5Ccdot%20x%20%2By%20%3D%20%5Cfrac%7B14%7D%7B5%7D)
![-2\cdot x +5\cdot y = 14](https://tex.z-dn.net/?f=-2%5Ccdot%20x%20%2B5%5Ccdot%20y%20%3D%2014)
The equation of the line in standard form is
.
3) By using the slope-intercept form, we obtain the equation of the line by direct substitution: (
,
)
![y = 3\cdot x +4](https://tex.z-dn.net/?f=y%20%3D%203%5Ccdot%20x%20%2B4)
The equation of the line in slope-intercept form is
.
Then, we obtain the standard form by algebraic handling:
![-3\cdot x +y = 4](https://tex.z-dn.net/?f=-3%5Ccdot%20x%20%2By%20%3D%204)
The equation of the line in standard form is
.
4) We begin with a system of linear equations based on the slope-intercept form: (
,
,
,
)
(Eq. 3)
(Eq. 4)
By applying (Eq. 4) on (Eq. 3), we find that the slope of the equation of the line is:
![-3\cdot m+6 = 0](https://tex.z-dn.net/?f=-3%5Ccdot%20m%2B6%20%3D%200)
![3\cdot m = 6](https://tex.z-dn.net/?f=3%5Ccdot%20m%20%3D%206)
![m = 2](https://tex.z-dn.net/?f=m%20%3D%202)
The equation of the line in slope-intercept form is
.
Then, we obtain the standard form by algebraic handling:
![-2\cdot x +y = 6](https://tex.z-dn.net/?f=-2%5Ccdot%20x%20%2By%20%3D%206)
The equation of the line in standard form is
.
5) We begin with a system of linear equations based on the slope-intercept form: (
,
,
,
)
(Eq. 5)
(Eq. 6)
From (Eq. 5), we find that:
![b = -2+m](https://tex.z-dn.net/?f=b%20%3D%20-2%2Bm)
And by substituting on (Eq. 6), we conclude that slope of the equation of the line is:
![5\cdot m -2+m = 3](https://tex.z-dn.net/?f=5%5Ccdot%20m%20-2%2Bm%20%3D%203)
![6\cdot m = 5](https://tex.z-dn.net/?f=6%5Ccdot%20m%20%3D%205)
![m = \frac{5}{6}](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7B5%7D%7B6%7D)
And from (Eq. 5) we find that the y-Intercept is:
![b = -2+\frac{5}{6}](https://tex.z-dn.net/?f=b%20%3D%20-2%2B%5Cfrac%7B5%7D%7B6%7D)
![b = -\frac{7}{6}](https://tex.z-dn.net/?f=b%20%3D%20-%5Cfrac%7B7%7D%7B6%7D)
The equation of the line in slope-intercept form is
.
Then, we obtain the standard form by algebraic handling:
![-\frac{5}{6}\cdot x +y =-\frac{7}{6}](https://tex.z-dn.net/?f=-%5Cfrac%7B5%7D%7B6%7D%5Ccdot%20x%20%2By%20%3D-%5Cfrac%7B7%7D%7B6%7D)
![-5\cdot x + 6\cdot y = -7](https://tex.z-dn.net/?f=-5%5Ccdot%20x%20%2B%206%5Ccdot%20y%20%3D%20-7)
The equation of the line in standard from is
.